Endogenous Regulation of Neural Stem Cells in the Adult Mammalian Brain - Coronas, Valerie (Central Nervous System Agents in Medicinal Chemistry, 2009)
Tissue-specific stem cells replenish organs by replacing cells lost due to tears and wears or injury throughout life. Long considered as an exception to this rule, the adult mammalian brain has consistently been found to possess stem cells that ensure neurogenesis. Neural stem cells persist within the subventricular zone bordering the lateral ventricles of the brain. Constitutively, neural stem cells proliferate and produce a continuous supply of new neurons that migrate towards the olfactory bulb where they ensure turnover of interneurons. Owing to their potential clinical use for the treatment of neurodegenerative diseases, the factors that control proliferation, self-renewal and differentiation of neural stem cells have received increasing interest. These studies have unraveled that the cellular dynamic within the subventricular zone is tightly controlled by astrocytes and endothelial cells that neighbor neural stem cells. These neighboring cells produce substrate- bound and soluble factors that make up a specialized microenvironment named the neurogenic niche. The equilibrium between neural stem cells activity and quiescence is adjusted by neurons located in remote brain areas that adapt neuron production to physiological and pathological constraints. Brain injury or neurodegenerative diseases affect neural stem cells proliferation, differentiation and migration suggesting that neural stem cells are involved in brain self-repair. Understanding the endogenous mechanisms that regulate neural stem cells will help to replenish cellular constituents lost by injury and thereby allow an effective development of neural stem cells based therapies of brain diseases.
Keywords: neurogenesis